Neotectonic Activity of Segmented Alluvial Fans Along Hemr in South Anticline, East Iraq - Al-Musawi, Hala A.; Abdallah, Hamed H.; Azzawi, Thair M. (Iraqi Journal of Science, 2020)
A quantitative analysis of geomorphic indices was carried out to understand the impacts of tectonics on the geomorphological relief of drainage basins and alluvial fans. Based on field work, satellite images and aerial photographs interpretation, five stages of alluvial fanswere recognized within the study area. Theyare of a coalesced type, forming continuous belt of Bajada, andcovering vast areas whichextend along the southwestern limb of Hemrinanticline. The alluvial fans’ sediments lie unconformably over pre- Quaternary sediments represented by angular unconformity.The earlier stages of the fanswere developed during the Plio- Pleistocene age, whereas the later stage represents the sediments of the Holocene age. Fourdistinct segmented alluvial fans were considered under this study, located within Torsaq and Shosharin basins. They aredeveloped in the first, second and third stagesof alluvial fans. Some morphotectonic parameters were calculated in order to understand the tectonic dynamics of these fans, includingmountain front sinuosity (Smf), ratio of valley floor’s width to height (Vf), fan tilting(β), and drainage basin asymmetry (FA). The results showedless active mountain frontand low uplift,according to the acquired high values of Vf.The fansare tilted towards the west direction, indicating uplift of their eastern parts,whilethe main streams are shifted downstream to the right.